2015
DOI: 10.3727/096368914x685276
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Forming Capacity and Biodistribution of Bone Marrow-Derived Stromal Cells Directly Loaded into Scaffolds: A Novel and Easy Approach for Clinical Application of Bone Regeneration

Abstract: In the context of clinical applications of bone regeneration, cell seeding into scaffolds needs to be safe and easy. Moreover, cell density also plays a crucial role in the development of efficient bone tissue engineering constructs. The aim of this study was to develop and evaluate a simple and rapid cell seeding procedure on hydroxyapatite/ b-tricalcium phosphate (HA/bTCP), as well as define optimal cell density and control the biodistribution of grafted cells. To this end, human bone marrow-derived stromal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In a classical approach, bone tissue engineering consists of harvesting bone marrow from a patient, isolating MSCs by their adherence to tissue culture plastic, expanding and differentiating those cells in culture to a sufficient number and then seeding them onto a suitable synthetic scaffold prior to implantation into the same patient. 38 39 40 41) The autologous approach to isolation and osteogenic differentiation of MSCs is however highly demanding in terms of logistics, production and safety of culture conditions, leading to a costly therapeutic procedure. The association of biomaterials and osteoprogenitor cells raises technical challenges (i.e., cell sources, types, doses, and timing) and regulatory issues (devices with medicinal drugs) for the implementation of clinical trials.…”
Section: Cytotherapy Of Hip Osteonecrosis: Challenges and Prospectsmentioning
confidence: 99%
“…In a classical approach, bone tissue engineering consists of harvesting bone marrow from a patient, isolating MSCs by their adherence to tissue culture plastic, expanding and differentiating those cells in culture to a sufficient number and then seeding them onto a suitable synthetic scaffold prior to implantation into the same patient. 38 39 40 41) The autologous approach to isolation and osteogenic differentiation of MSCs is however highly demanding in terms of logistics, production and safety of culture conditions, leading to a costly therapeutic procedure. The association of biomaterials and osteoprogenitor cells raises technical challenges (i.e., cell sources, types, doses, and timing) and regulatory issues (devices with medicinal drugs) for the implementation of clinical trials.…”
Section: Cytotherapy Of Hip Osteonecrosis: Challenges and Prospectsmentioning
confidence: 99%
“…This density does not seem to be a limiting factor. Indeed, the best results in several similar studies were obtained on granules with densities ranging from 90,000 to 125,000 cells per milligram (Léotot et al, ; Mankani, Kuznetsov, Fowler, Kingman, & Robey, ; Mebarki et al, ). It should be noted, however, that the presence or absence of vessels was not assessed in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…New bone formation (osteoids) was analysed on H&E stained sections. The relative surface area occupied by osteoids (%) was quantified on 15 sections (regardless of the implantation site because the results were the same for both subcutaneous and intramuscular implants) for each condition (empty scaffold; scaffold seeded with WJMSC‐OBs; scaffold seeded with WJMSC‐OBs + ECs), using ImageJ software (National Institutes of Health), as described previously by Léotot et al (). The total implant area was selected, and osteoid area was calculated as a percentage of the total area.…”
Section: Methodsmentioning
confidence: 99%
“…Careful pathologic assessments of retrieved grafts in humans have shown that the primary mode of union is via external host-derived callus which bridges the host-graft interface and leads to cortical -cortical and cancellous -cancellous bone union [25,26,11,19]. There is a gradual process of creeping replacement which works inward from the hostgraft junction toward the middle of the graft at a gradual rate [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%